A Synthesizable IP Core for DVB-S2 LDPC Code Decoding - Kienle, Frank; Brack, Torben; Wehn, Norbert (Design, Automation and Test in Europe, 2005)
The new standard for digital video broadcast DVB-S2 features Low-Density Parity-Check (LDPC) codes as their channel coding scheme. The codes are defined for various code rates with a block size of 64800 which allows a transmission close to the theoretical limits. The decoding of LDPC is an iterative process. For DVB-S2 about 300000 messages are processed and reordered in each of the 30 iterations. These huge data processing and storage requirements are a real challenge for the decoder hardware realization, which has to fulfill the specified throughput of 255MBit/s for base station applications. In this paper we will show, to the best of our knowledge, the first published IP LDPC decoder core for the DVB-S2 standard. We present a synthesizable IP block based on ST Microelectronics 0:13µm CMOS technology.